2015
DOI: 10.1016/j.bbrc.2015.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Two specific membrane-bound aminopeptidase N isoforms from Aedes aegypti larvae serve as functional receptors for the Bacillus thuringiensis Cry4Ba toxin implicating counterpart specificity

Abstract: The interaction between Bacillus thuringiensis Cry toxins and their receptors on midgut cells of susceptible insect larvae is the critical determinant in toxin specificity. Besides GPI-linked alkaline phosphatase in Aedes aegypti mosquito-larval midguts, membrane-bound aminopeptidase N (AaeAPN) is widely thought to serve as a Cry4Ba receptor. Here, two full-length AaeAPN isoforms, AaeAPN2778 and AaeAPN2783, predicted to be GPI-linked were cloned and successfully expressed in Spodoptera frugiperda (Sf9) cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…gambiae (Zhang et al, 2008) and Aedes aegypti (Aroonkesorn et al, 2015;Chen et al, 2009;Chen et al, 2013). The apparent sizes of several identified APNs suggested proteolytic degradation and/or formation of dimers with high-molecular weight.…”
Section: Discussionmentioning
confidence: 99%
“…gambiae (Zhang et al, 2008) and Aedes aegypti (Aroonkesorn et al, 2015;Chen et al, 2009;Chen et al, 2013). The apparent sizes of several identified APNs suggested proteolytic degradation and/or formation of dimers with high-molecular weight.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we have shown that the stability of two receptor-binding hairpins (i.e., β 2 -β 3 and β 4 -β 5 within Cry4Ba-DII) contributed by hydrogen bonding between Thr 328 -Thr 369 side-chains is important for toxin binding to Cyt2Aa2—an alternative receptor for the Cry4Ba toxin [ 17 , 18 ]. Furthermore, we have succeeded in identifying two different types of Cry4Ba receptors from Aedes mosquito larvae, i.e., glycosylphosphatidylinositol (GPI)-anchored alkaline phosphatase and GPI-anchored aminopeptidase N (APN) [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Insect M1 peptidases are mainly expressed in the gut, where they play important intermediate roles in protein digestion [ 111 ] as well as host-pathogen interactions. Membrane-bound aminopeptidases in the gut are receptors for Bacillus thuringiensis toxins in several insect species [ 112 114 ]. Aminopeptidases have also been detected in other insect tissues, such as the fat body [ 115 ], salivary glands [ 116 ], and Malpighian tubes [ 116 ].…”
Section: Resultsmentioning
confidence: 99%